CURRENT STATE OF FISHERIES AND ASSESSMENT OF FISH STOCKS IN THE WESTERN MIDDLE OF THE CASPIAN SEA. PROSPECTS FOR THE USE OF THE FISH RESOURCES - A. S. Abdusamadov; S. A. Guseinova; L. A. Dudurkhanova (Юг России: экология, развитие, 2016)
Aim. To aim is to assess stocks and the fisheries of aquatic biological resources in the western part of the middle Caspian Sea and perspectives for the use of their resource potential.Methods. On the basis of the literature sources and our own data on the fish inventory in the western part of the Middle Caspian, we discuss possible reasons for emerging environmental, economic and other problems in the use of biological resources.Results. The main negative factors are the large-scale poaching, resulting in a catastrophic reduction in stocks of sturgeon and other valuable fish species of the Caspian Sea, a natural penetration of alien organisms (Mnemiopsis) and overfishing of some species. The potential danger is large-scale development of oil and gas fields in the Caspian Sea, which can lead to even worse situation for the biological resources of the sea.Conclusions. In order to preserve the biological resources of the sea it is necessary to create conditions for steadily developing fishing and fish processing enterprises, thus ensuring the satisfaction of the constant demand for fish products and an increase in the revenue base of the budget and the well-being of the Russian population.